Tingkat Penerimaan Panelis Terhadap Sifat Organoleptik Sabun Transparan Yang Diformulasi Dari Minyak Sawit Dengan Penambahan Pewarna dan Pewangi - Suwito '; Raswen Efendi; Rahmayuni ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Transparent soap is produced by reaction between natrium or potassium with oil vegetarian or oil animals, transparent soap manufacturing in Indonesia have not optimals and still difficult to find in the market. Addition of colour and deodorant aim to to more upgrade esthetics and assess to sell of society. One of reason of election of the deodorant and colour because more interesting and impress by experience. Existence soap in the middle of society of vital importance in assessment by organoleptik, cause of assessment of organoleptik can improve, repair product , looking after quality and know level of panelist identification. Intention of this research is acceptance of panelist to nature of organoleptik of transparent soap which formulation between palm oil with addition of colourant and deodorant.   The studies were conducted with organoleptic test. This research used completely randomized design with six treatments and twenty replications. Data obtained were treated by the analysis of variance followed by duncan test. The test hedonik, addition colours and perfumes of transparent soap give real influence to colour and perfume, but give influence is not real to a lot of spume, tekstur, and assessment is overall. Colour which prefer that is red colour with trawberry perfume, perfume which prefer that is treatment blue colour green tea perfume.   Keyword: transparent soaps, colour soap, perfume soap, and vegetables oil soap.